The DNA-dependent RNA-polymerase of Thermotoga maritima; characterisation of the enzyme and the DNA-sequence of the genes for the large subunits. - Palm, P (1993)
An improved purification procedure for Thermotoga maritima RNA-polymerase holoenzyme was developed. The enzyme is highly active with poly dAT or T7 phage DNA as template. DNA gyrase was found to be a side product of this RNA-polymerase purification. The genes for the large subunits beta and beta' of RNA-polymerase were cloned and sequenced. The phylogenetic position of T.maritima within the bacterial domain was determined by various methods. It is the lowest bacterial offspring but slightly higher than the chloroplasts.